Confiscation of Personal Assets of Corruption Defendants in a Positive Legal Perspective - Kholik, Ibnu; ., Ediwarman; Ekaputra, M; Mulyadi, Mahmud (KnE Social Sciences, 2024)
One-of-a-kind efforts to make the losses state’s financial incurred by the State due to corrupt activities, is through the confiscation of the Defendant’s assets. Later it may subsequently be utilized for a form of monetary payment in lieu of State losses charged to the Defendant. On the grounds of payment of money in lieu of State losses, confiscation of the Defendant’s personal assets that had nothing to do with corruption was then carried out. The research’s main eligibility is to find out how significance proof is involved due to tribunal mechanism, as in the safetymeasureness of the defendant given right and assets as being regulated for evidences in the tipikor case. The researcher’s study applied juridical normative method employing statutory and conceptual pathways. Secondly, layered information was gathered from observation and papers, in order to ensure the quality. According to the researcher’s findings, the purpose of headlining deposition in tribunal is to support the proof of the litigant’s motion, incapable of assuring the sentence’s delivery. There is a guarantee and protection of property rights in the Indonesian constitutional written law 1945 (28H) par. (4). It demonstrates the litigant’s possession of their property being safeguarded by the state, which had unassociated an elicit act of graft as property sheltered from confiscation in the court process. Unlike the personal property of the litigant, if is employed in an unlawful conduct as graft itself, the belongings shall be seized within the tribunal proceedings. Keywords: protection, asset, evidence, confiscation